Profitabilitas dan Peluang Pengembangan Agroindustri Gula Kelapa dalam Sistem Agribisnis Kelapa (Cocos nucifera L.): Suatu Kasus Di Desa Sukanagara Kecamatan Lakbok Kabupaten Ciamis - Tito Hardiyanto (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2020)
Coconut sugar agro-industry is one of the important commodities as a reliable source of income. This study aims to determine: (1) Profitability and profitability of the coconut sugar agro-industry business; and (2) Opportunities for developing coconut sugar agro-industry in Sukanagara village, Lakbok District, Ciamis Regency. The method used is a survey method, by taking the case of farmers who coconut sugar business in the village of Sukanagara, Lakbok District, Ciamis Regency. The research location is Sukanagara village with consideration of the results of these studies can provide solutions to increase coconut sugar production capacity to be in harmony with other villages. Determination of farmer respondents was conducted by census of 31 farmers. Analysis tools to determine the profitability of coconut sugar agro-industry can be seen from the costs incurred and the revenue generated in the production process, while the development opportunities are seen from the income and level of employment. The results showed that: (1) The use of total costs (production costs) in the coconut sugar agro-industry in the production process was Rp. 78,264.57 and Rp. 101,100. (2) The opportunity for developing coconut sugar agro-industry in Desa Sukanagara village is quite promising because the coconut sugar agro-industry is able to generate a profit of 29.18 percent of the capital spent in one production process. In addition, employment in the coconut sugar agroindustry in Sukanagara Village is 2.47 percent of the village workforce, although the percentage is small, it has been able to contribute to employment in Sukanagara Village.